2000
DOI: 10.1006/dbio.2000.9856
|View full text |Cite
|
Sign up to set email alerts
|

MGF (KIT Ligand) Is a Chemokinetic Factor for Melanoblast Migration into Hair Follicles

Abstract: Melanoblasts, the precursors of the pigment-producing cells of the skin and hair, are derived from the neural crest and migrate to the skin around 12 days of gestation in the mouse. In adult mice almost all the melanoblasts are confined to the hair follicles except for the epidermal layers of nonhairy skin. The receptor tyrosine kinase, KIT, is necessary for the survival, proliferation, and migration of melanoblasts. We have utilised an organ culture for embryonic skin taken from Dct-lacZ transgenic mice. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
85
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(92 citation statements)
references
References 44 publications
7
85
0
Order By: Relevance
“…1G), suggesting that these cells constitute RPE. When these RPE-like cells were derived from ES cell lines established from transgenic mouse embryos containing a fusion construct formed with the transcriptional control sequence of the pigment cell-specific Dct (DOPAchrome tautomerase) gene and the lacZ reporter (Jordan and Jackson, 2000), they expressed lacZ activity, further supporting the view that these cells represent RPE (Fig. 1H).…”
Section: Morphology Of the Eye-like Structures Induced From Es Cellsmentioning
confidence: 55%
“…1G), suggesting that these cells constitute RPE. When these RPE-like cells were derived from ES cell lines established from transgenic mouse embryos containing a fusion construct formed with the transcriptional control sequence of the pigment cell-specific Dct (DOPAchrome tautomerase) gene and the lacZ reporter (Jordan and Jackson, 2000), they expressed lacZ activity, further supporting the view that these cells represent RPE (Fig. 1H).…”
Section: Morphology Of the Eye-like Structures Induced From Es Cellsmentioning
confidence: 55%
“…Between embryonic day (E) 10 and E16.5, melanoblasts migrate from the neural crest to the dermis, and then to the epidermis [15][16][17] . The Dct-lacZ transgene is expressed in melanoblasts as soon as they leave the neural crest and persists through most developmental stages and in epidermal melanocytes 17,18 . We observed more lacZ-positive cells in Gnaq Dsk1/+ and Gna11 Dsk7/+ embryos beginning at the earliest stage at which melanoblasts can be detected (E10.5; Fig.…”
Section: Dsk1 and Dsk7 Act Additively And Quantitativelymentioning
confidence: 99%
“…This finding suggests that these genes are necessary for melanoblast survival and/or for their dispersal from the migration staging area. Jordan and Jackson (2000) have shown that, whereas Kitl acts as a chemokinetic factor that accelerates melanoblast movement to the hair follicles, it does not have chemoattractive abilities.…”
Section: Development Of the Melanocytementioning
confidence: 99%